Function after Wrist Arthrodesis with Non-Vascularized Fibular Graft in Distal Radius Giant Cell Tumor: Case Series - Heru Rahmadhany (Cermin Dunia Kedokteran, 2022)
Giant cell tumor (GCT) of bone, the most common benign locally aggressive bone tumor, accounts for 4% to 5% of all primary bone neoplasms and 20% of benign bone tumors. The distal radius is the third commonest site of involvement in about 10% of GCT cases. Due to the high recurrence rate after curettage of the more progressed lesions, most surgeons prefer en bloc resection followed by reconstruction. Cases: Three distal radius GCT Campanacci III cases underwent en bloc resection and wrist arthrodesis with non-vascularized fibular graft. The mean follow-up period was nine months (6-12 months). Patients were evaluated with the Disabilities of the Arm, Shoulder, and Hand (DASH) Score. Results: Union had been achieved in 2 patients, and implant removal was done. One patient needs cancellous bone grafting after implant removal—no sign of recurrence after one year. DASH score showed moderate disability. Conclusion: Autogenous non-vascularized fibular graft reconstruction can be considered a reasonable option after en bloc resection of distal radius GCT. Giant Cell Tumor (GCT) adalah tumor tulang jinak yang paling sering dijumpai, bersifat agresif secara lokal, merupakan 4-5% dari seluruh neoplasma tulang primer dan 20% dari seluruh tumor tulang jinak. Radius distal merupakan lokasi GCT terbanyak ketiga, mencakup 10% kasus GCT. Mengingat tingginya rekurensi setelah prosedur kuretase, lebih disukai reseksi en bloc diikuti rekonstruksi. Kasus: Tiga pasien GCT pada radius distal (Campanacci III) menjalani reseksi en bloc disertai arthrodesis pergelangan tangan. Follow-up rata-rata selama 9 bulan (range 6-12 bulan). Pasien dinilai menggunakan skor Disabilities of the Arm, Shoulder, and Hand (DASH). Hasil: Union tulang tercapai pada 2 pasien, dan implan telah dicabut. Satu pasien membutuhkan graft dari tulanag cancellous setelah pencabutan implan. Tidak didapatkan rekurensi pada periode follow-up satu tahun. Skor DASH menunjukkan disabilitas sedang pada ketiga pasien. Simpulan: Prosedur rekonstruksi menggunakan nonvascularized fibular graft baik dilakukan setelah reseksi en bloc pada pasien GCT radius distal.